Didactic strategies in English language teaching: analysis of the implementation of the didactic activities related to multiple intelligences in seventh grade in a public school in Armenia, Quindío (2018)
In this research is contained are didactic strategies used to teach English to seventh graders in order to contribute in their learning process. This action research aimed to analyze how didactic strategies related with multiple intelligences benefit the process of teaching English to seventh graders at a public school in Armenia. It consists on a didactic intervention carried out during twelve sessions in which researchers taught seventh grade topics through games, art, music, teamwork activities including multiple intelligences. The most common used intelligences were interpersonal and intrapersonal, however all of them were included during the classes. Also, motivation and students’ performance was directly related with the variety of exercises presented during the lessons. Furthermore, students’ perception about English and it importance was documented.